Layla [compact disc, unabridged] - Hoover, Colleen (Brilliance Audio, Inc., 2020)
When Leeds meets Layla, he's convinced he'll spend the rest of his life with her, until an unexpected attack leaves Layla fighting for her life. After weeks in the hospital, Layla recovers physically, but the emotional and mental scarring has altered the woman Leeds fell in love with. In order to put their relationship back on track, Leeds whisks Layla away to the bed-and-breakfast where they first met. Once they arrive, Layla's behavior takes a bizarre turn. And that's just one of many inexplicable occurrences. Feeling distant from Layla, Leeds soon finds solace in Willow, another guest of the B&B with whom he forms a connection through their shared concerns. As his curiosity for Willow grows, his decision to help her find answers puts him in direct conflict with Layla's well-being. Leeds soon realizes he has to make a choice because he can't help both of them. But if he makes the wrong choice, it could be detrimental for all of them.